Loves of a blonde [videorecording (DVD)] - Forman, Miloš; Brejchová, Jana, 1940-; Pucholt, Vladimír, 1942- (Criterion collection (DVD videodiscs), 2002)
In a small factory town not far from Prague, women outnumber men ten to one, presenting problems for teens entering womanhood, as they seek to learn about real life and love.